Prevalence of physical activity and its association with body mass index among late adolescents in Kuantan, Malaysia - Jamani, Nurjasmine Aida; Said, Abdul Hadi; Abd Aziz, Karimah Hanim; Abd Rahman, Mohd Aizuddin (2019)
A national data reported more than half of school going adolescents in Malaysia were physically inactive. This study aimed to describe the prevalence of physical activity among late adolescent in Kuantan, Malaysia and to determine factors associated with their physical activity level. A cross sectional study among late adolescents aged 17 - 19 from seven governmental higher learning institutions in Kuantan, Malaysia was conducted from April to October 2018. A validated, selfadministered International Physical Activity Questionnaire (IPAQ) questionnaire was used to measure the level of physical activity among participants. Weight and height of the participants were measured and the body mass index (BMI) was calculated. Chi-square test was used to test for association between physical activity level and BMI of the participants. The association between physical activity and socio-demographic profile was tested using logistic regression analysis. One third of the participants (37.6 %) have high physical activity level while 29.0% of them only practiced low physical activity level. Non-smokers were 0.4 times more physically active than smokers (aOR 0.39, 95% CI 0.19-0.78) while male gender was 2.46 times more active than female (aOR 2.46, 95% CI 1.55-3.92). There was no statistically significant association between physical activity level with BMI of the participants (2 = 0.93, p = 0.63). Only one third of late adolescents in our study practiced high level of physical activity. This is worrying as it may leads to increased number of morbidity and mortality related to low physical activity. Furthermore, physical activity level during adolescence-age group may influenced their physical activity level during adulthood. Therefore, continuous health education focused on the important of physical activity is undoubtedly crucial. Smokers were found to be less physically active than non-smokers. Hence, health education focused on the important of physical activity and the harm of smoking should be targeted simultaneously. Clinical